Resilient Home Design for A Coastal Community of Baan Khun Samut Chin, Samutprakan - Phattanawasin, Srisak; Boonlue, Wisan (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
Over the last 50 years, Baan Khun Samut Chin village in Samutprakan has long struggled against the rapid erosion of their coastline along the Upper Gulf of Thailand and the forthcoming loss of their entire territory. This serious problem affected to economics, society, way of life, and especially an existence of coastal community. This research proposed an experimental prototype of resilient house design to confront the erosion disaster for the Baan Khun Samut Chin community. By analyzing the problems of physical environment, social, culture, economic factors and construction techniques along with site surveying as well as reviewing theories and other related design projects, the architectural design concept with appropriate solutions was proposed. The proposed design concepts were including 1) durable design by integrating the floating platform of buoyancy structure above the flood line to the fixed structural 4-stilts supporting the light-weight roof, 2) resilient design for 3-meters sea level rising in next 30 years, and 3) low-cost design by choosing local materials and modular coordinating to prefabricated size of building elements. The experimental design of resilient home is expected to be a solution for Baan Khun Samut Chin community and those communities facing the same issues and government agencies with an urgent need for a ready and effective remedy.